DISPENSASI PERKAWINAN DI INDONESIA : ANALISIS PLURALISME HUKUM DI PENGADILAN AGAMA DARI PERSPEKTIF HUKUM KELUARGA ISLAM - Asman, Asman (El-Ahli : Jurnal Hukum Keluarga Islam, 2025)
The dispensation of underage marriage is an important issue in the legal and child protection system in Indonesia. Although Law Number 16 of 2019 has set the minimum age of marriage for men and women to 19 years, the practice of granting dispensation is still rampant. This dispensation is filed through religious courts for Muslims and state courts for non-Muslims on urgent grounds such as out-of-wedlock pregnancies or socio-cultural pressures. This study uses a normative-comparative approach by analyzing national regulations and principles of Islamic Family Law, including references to the Compilation of Islamic Law (KHI), fiqh nikah, and sharia maqashid. The results showed that the majority of dispensation requests were due to unplanned pregnancies and family pressure, which impacted the child's reproductive health, psychological condition, and education. From the perspective of sharia maqashid, this practice is often contrary to the goals of the protection of the soul (hifz al-nafs), heredity (hifz al-nasl), and reason (hifz al-'aql). This study identified  a research gap in the form of a lack of harmonization between the application of Islamic law and national law in the protection of children from the practice of early marriage. Academically, this research contributes to the development of the study of Islamic Family Law by offering a more integrative child protection paradigm, based on sharia maqashid, and in line with national legal policies. This research contributes to understanding the harmonization of Islamic Family Law and national law in protecting minors, emphasizing the urgency of holistic approaches through education, legal enforcement, and community awareness to prevent early marriage.